2019
DOI: 10.1152/ajprenal.00424.2018
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-proteome integration of archival human renal cell carcinoma biopsies enables identification of molecular mechanisms

Abstract: Renal cell cancer is among the most common forms of cancer in humans, with around 35,000 deaths attributed to kidney carcinoma in the European Union in 2012 alone. Clear cell renal cell carcinoma (ccRCC) represents the most common form of kidney cancer and the most lethal of all genitourinary cancers. Here, we apply omics technologies to archival core biopsies to investigate the biology underlying ccRCC. Knowledge of these underlying processes should be useful for the discovery and/or confirmation of novel the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…The highest positive correlations indicate that immune responses play a central role, mostly due to immune cell infiltration and immunotherapy treatment. The protein organization in the membrane changes the capacity of the motility of the cell, and both events have been described in this type of cancer previously [42]. The observed biological categories that anti-correlate with the proteomics (and transcriptomics) data show important effects centered in the metabolism and the respiratory chain in the cell, indicating decoupling between the respiratory chain and metabolism in the cell, as expected in many types of cancer [43,44].…”
Section: Discussionmentioning
confidence: 58%
“…The highest positive correlations indicate that immune responses play a central role, mostly due to immune cell infiltration and immunotherapy treatment. The protein organization in the membrane changes the capacity of the motility of the cell, and both events have been described in this type of cancer previously [42]. The observed biological categories that anti-correlate with the proteomics (and transcriptomics) data show important effects centered in the metabolism and the respiratory chain in the cell, indicating decoupling between the respiratory chain and metabolism in the cell, as expected in many types of cancer [43,44].…”
Section: Discussionmentioning
confidence: 58%
“…Search on PRoteomics IDEnti cations database (PRIDE) (https://www.ebi.ac.uk/pride/) 44 form 2019 to 2020 led to identifying three RCC studies that each of them included the proteomics information of one of the RCC subtypes and adjacent normal tissues. The results of proteomics analysis were downloaded from the supplementary information of their published articles 37,45,46 . Venn diagram analysis was performed to nd common signi cant differential proteins in three subtypes of RCC by OriginPro 2019 (https://www.originlab.com/2019, OriginLab Corporation, Northampton, MA, USA).…”
Section: Data Source and Network Analysismentioning
confidence: 99%
“…The RCC incidence rates have been increasing during the decade 3 . According to the American Cancer Society, an estimated 73,750 new cases (45,520 in males and 28,230 in females) and 14,830 deaths (9,860 in males and 4,970 in females) from RCC will occur in 2020 4 . If cancer has not metastasized, the 5-year survival rate is 65-90%, but this is lowered considerably when cancer has spread so that the 5-year survival rates for patients with stage IV disease are less than 20% 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in this particular dataset, CFL1, PFN1, and ALDOA were found to be decreased in early stages relative to NATs. In another study, FFPE ccRCC tissues and patient matched NATs that were previously characterized at the transcript level, were characterized at the protein level, wherein the authors found disparate cellular pathways over-represented at each biological domain [50]. At the protein level, metabolic pathways were robustly shown to be altered, whereas transcriptomics indicated immune response pathways were more significantly impacted.…”
Section: Ccrcc Tissue Profilingmentioning
confidence: 99%